Cover Image. (20th May 2022) - Kim, Jong‐Hui; Lee, Eun‐Seon; Kim, Bu‐Min; Ham, Jun‐Sang; Oh, Mi‐Hwa
Abstract : The cover image is based on the Research Article Broad‐spectrum antimicrobial activity of cinnamoyl esterase‐producing Lactobacilli and their application in fermented rice bran by Mi‐Hwa Oh et al., https://doi.org/10.1002/jsfa.11654 Abstract : The cover image is based on the Research Article Broad‐spectrum antimicrobial activity of cinnamoyl esterase‐producing Lactobacilli and their application in fermented rice bran by Mi‐Hwa Oh et al., https://doi.org/10.1002/jsfa.11654